Electrolyte induced electrical dis-connection between single graphene nanoplatelets and an electrode - Krittayavathananon, A; Li, X; Batchelor-Mcauley, C; Sawangphruk, M; Compton, R (American Chemical Society, 2018)
We report the influence of electrolyte on the electrical contact between graphene nanoplates (GNPs) and an electrode via a single entity electrochemical technique. The current 'steps' were observed in the absence of electrolyte due to the GNPs impacting on and bridging across an interdigitated gold electrode array (IDE), in contrast current spikes of short duration were obtained in the presence of electrolyte. This result indicates that in the latter case the constant short circuit bridging current was switched off and replaced solely by impacts of GNPs with single electrodes. These observed current spikes measured in the presence of electrolyte are evidenced to be of a capacitative nature, demonstrating the high sensitivity of the electronic properties of the GNPs/metal junction to the ionic strength of the electrolytic solution.